The Role of Digital Literacy in Preventing Cybercrime Among Adolescents: A Social Study in Urban Areas - Risma, Siti Sya'ada Alda; Fachuda, Fatimah Azzahro (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study discusses the theoretically relevant concepts and the objectives of preventing cybercrime among adolescents in urban settings; technically, the author perceives this as of paramount importance, as adolescents are being conditioned to view themselves as victims due to a lack of awareness of cybercrimes. The significant target populations in this study include 384 adolescents randomly selected from Jakarta, Bandung, and Surabaya. Their levels of digital literacy were assessed using quantitative research methods, including the distribution of structured questionnaires. It aims to develop a construct of digital literacy in the technical, cognitive, social, and ethical domains. The study established a meaningful statistical association (r = 0.642; p < 0.001), indicating that 41.2% of the variance in cybercrime prevention ability is explained by digital literacy. Based on the significant findings, it can be stated that there is strong technical skill, whereas there remains a weak understanding of digital ethics and privacy. Regarding theory, this research has added a social dimension to the understanding of digital literacy and, in practice, has identified the need for educational interventions, community programs, and the upgrading of public policy to promote adolescent digital literacy. This implies that the findings would draw attention to the urgent need for a national digital literacy strategy integrated into a curriculum for schools, public campaigns for awareness, and the regulation of data protection with a scope of work. Such would create a safe and ethical space for adolescents in a digital world